Design and Implementation of a Low Cost USB Duplicator - Muhammad Usman Rashid; Zeashan Hameed Khan (Bulletin of Electrical Engineering and Informatics, 2012)
USB devices and flash disks are the most common storage device being used but very little work has been done on it at university project level. Considering the increasing capacity and popularity of USB flash disks, it is believed that in the near future they will replace CDs/DVDs and will be used as a primary storage medium. For this purpose, a USB flash disk duplicator will also be required just as a CD/DVD duplicator is required today. The aim of the present work is to develop a portable and stand-alone device capable of copying the contents of one USB flash disk/mass storage device to another USB flash drive without the use of an intermediary computer.